Perancangan Sistem Informasi Manajemen Proyek: Sistem Informasi Kontraktor - Yuliana Sari Harahap; Irwan Padli Nasution (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Effective project management is a key factor for success in the construction industry, especially for contractor companies managing multiple projects simultaneously. Common issues often encountered include lack of coordination, delayed information flow, and difficulties in monitoring project progress in real-time. This study aims to design an integrated project management information system to support the operational activities of contractors, ranging from planning and execution to project reporting. The methodology used is the waterfall approach, starting from system requirements analysis, design, implementation, and testing. The result of this study is a web-based information system prototype capable of managing project data, scheduling, resources, and project performance reports. It is expected that this system can improve efficiency, information accuracy, and decision-making in contractor project management.